Learning from teaching: pre-service primary teachers' perceived learning from engaging in formal Lesson Study. Issue 3 (3rd July 2019) - Hourigan, Mairéad; Leavy, Aisling M.
Abstract : While there is abundant research reporting the impact of Lesson Study as a professional development framework for qualified teachers, its potential within initial teacher education remains relatively unexplored. We present a particular model of formal Lesson Study which has been experienced annually for a decade by Irish pre-service primary teachers. This study examines the perceived effects on learning of this Lesson Study model on a large sample of pre-service primary teachers ( N  = 225) who worked in 45 different lesson study groups over a 10 year period (2008–2017). Data analysis reveals that participants' perceptions of learning fell within two distinct themes namely 'An awakening regarding teacher content knowledge' and 'Cornerstones of learner-centred practice', each of which consisted of rich inter-connected sub-themes. As a result of engaging in Lesson Study, participants report an increased awareness of the importance of deep content knowledge in addition to adopting a learner-centred approach to their practice. Participants also believed that Lesson Study enhanced their professional knowledge and skills in the curricular area of focus (mathematics, in this case). While this study focuses on self-report data, these opinions are fundamental given research which proposes that interventions will fail if participants judge them to be ineffective.